Developmental aspects in models of behaviour and education - Potočárová, Mária (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The article points out the link between the evolutionary conditioned human personality development and their upbringing. Basing on this theoretical context can be derived the definition of relational bonding, behavioral relationships, especially in the early childhood, as well as other patterns of behavior during individual (human) development. The models of behavioral patterns are demonstrated in both negative and positive forms in the adolescent youth. Although high importance is assigned to the socializing influence in the adolescent age, the innate natural relations of the development and evolutionary determined specific signs of relational bonding play a significant role in this period of the human development. The undesirable formulas and various forms of problem behavior must then be solved through the reeducational upbringing processes, in particular using the interacting in the educational process, communication, "relational" education and cultivating personality formation. The goal of the education is the development and integrity of the personality.

W artykule zwrócono uwagę na powiązanie między ewolucyjnie uwarunkowanym rozwojem osobowości człowieka a jego wychowaniem. Na podstawie tego kontekstu teoretycznego można wyprowadzić definicję więzi relacyjnej, relacji behawioralnych, zwłaszcza we wczesnym dzieciństwie, a także innych wzorców zachowań w indywidualnym rozwoju człowieka. Modele wzorców behawioralnych są demonstrowane zarówno w formie negatywnej, jak i pozytywnej u dorastającej młodzieży. Chociaż duże znaczenie przypisuje się wpływowi socjalizacji w wieku dorastania, to wrodzone naturalne relacje rozwojowe i ewolucyjnie zdeterminowane specyficzne oznaki więzi relacyjnej odgrywają kluczową rolę w tym okresie rozwoju. Niepożądane formuły i różne formy zachowania problemowego muszą być wyeliminowane poprzez proces reedukacji, szczególnie z wykorzystaniem interakcji w procesie edukacyjnym, komunikacji, edukacji „relacyjnej”, poprzez pracę nad formowaniem osobowości. Celem edukacji jest rozwój i integralność osobowości.
Aspekty rozwojowe w modelach behawioralnych a edukacja
Keywords: evolution; human personality; behavior models; education and upbringing process; ewolucja; osobowość; modele behawioralne; proces edukacji i wychowania